Bâtir le manifeste : de La Città Nuova d’Antonio Sant’Elia au manifeste architectural contemporain - Viviana Birolli (Itinéraires, 2018)
The article explores some of the milestones in the history of the architectural manifesto: from Antonio Sant’Elia’s Futurist manifesto (1914) to the anthologies of the first decade of the twenty-first century, through Rem Koolhaas’ retroactive manifesto (1978). Two graphs from the Manart database are the starting point for questioning the manifestos’ definitional difficulties, especially regarding its recent developments in terms of form and function. The links between the history of manifestos and the evolution of its notion are then outlined, a dynamic situated at the crossroads between textual production and critical reception. Following the renewed interest for the manifesto in architecture—the forms of which are yet to be explored—this paper puts into perspective the idea, introduced by the 1980s, that the manifesto has become an obsolete format.